2000
DOI: 10.1680/geot.2000.50.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular state variables and stress–strain behaviour of silty sands

Abstract: Relative contributions by the coarser and finer grains in a silty sand to its stress–strain response are affected by the intergranular matrix structure. The nature of this contribution is illustrated using an intergranular matrix phase diagram in terms of void ratio (e), fines content (FC), and intergranular and interfine void ratios (es and ef). New intergranular state parameters (ψs, ψf) and (es, ef) are introduced as state variables to characterize silty sands; es and ef dictate the steady-state characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(107 citation statements)
references
References 24 publications
3
101
0
3
Order By: Relevance
“…For mixtures with highˆnes contents, when the sand grains become isolated (VSAND may be ignored), the interne void ratio, ef, may be a more appropriate parameter to be used (Thevanayagam and Mohan, 2000):…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…For mixtures with highˆnes contents, when the sand grains become isolated (VSAND may be ignored), the interne void ratio, ef, may be a more appropriate parameter to be used (Thevanayagam and Mohan, 2000):…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Coop and Lee 1993), some uncertainties still remain in describing the behaviour of binary mixtures (e.g. Thevanayagam and Mohan 2000). For example, there is agreement (e.g.…”
mentioning
confidence: 99%
“…However, it is less clear what this value of fines should be for different soils (Zuo and Baudet 2015) and how the nature of the fines influences the mechanics of compression. The approach proposed by Thevanayagam and Mohan (2000) suggests using the traditional definition of void ratio at the two mixture extremes and an inter-granular or inter-fine void ratio for intermediate cases, depending on whether the mechanics are fines or coarse grain-dominated, but it remains rather subjective when to use one definition or the other as the transitional fines content is highly variable and difficult to predict (Zuo and Baudet 2015). This type of approach may also only be used if the particle size distribution is binary and there is sufficient separation of the two grading sizes.…”
mentioning
confidence: 99%
“…The properties of these soils, which are called as intermediate soils, vary because of the density and mixture content. Difficulties arise in understanding their stress-strain behaviour, compression mechanism, and liquefaction potential [1][2][3][4][5][6][7][8][9][10][11]. For example, Vallejo and Mawby [12] reported that shear strength of the clay-sand mixtures is fully controlled by the sand below 25% of fines content.…”
Section: Introductionmentioning
confidence: 99%